ETHNOBOTANICAL STUDY OF BERANGAN (Castanopsis spp.) IN NAGAN RAYA DISTRICT INDONESIA - Rizza Amanda Phonna; Saida Rasnovi; Dahlan Dahlan; Firman Rija Arhas; Hendrix Indra Kusuma (Universitas Islam Negeri Ar-Raniry, 2023)
Castanopsis spp., also known as berangan in Acehnese, is a chestnut species that is still used and well-known by the people of Indonesia. However, it is currently very rare and is becoming less well-known to today's younger generation. This research aims to study and understand how people in Nagan Raya process and use Castanopsis spp. species. Data were collected using two methods: ethnobotanical data and population data. The participatory rural appraisal (PRA) method was used in direct interviews to collect ethnobotanical data. Purposive sampling was used to obtain the Castanopsis spp. the population as much as local informants could show. There were 48 people from three groups of respondents who provided ethnobotanical data: traditional figures, farmers, and villagers who Castanopsis spp. species. The respondents in this study were divided into three groups based on their age, education, and occupation. There are 2 types of Castanopsis spp. that have been found in the Nagan Raya district, Castanopsis inermis and Castanopsis costata. They were discovered in forest areas, plantations, office/home yards, and roadside areas. Castanopsis spp fruits are commonly used as food, while the wood are usually used as carpentry/furniture wood and firewood. Kata Kunci: ethnobotany, berangan, chestnut, Castanopsis spp.